1952
DOI: 10.1113/jphysiol.1952.sp004789
|View full text |Cite
|
Sign up to set email alerts
|

Vascular reactions to histamine, histamine‐liberator and leukotaxine in the skin of guinea‐pigs

Abstract: A substantial increase in capillary permeability is a feature of acute inflammation in bacterial infections. The present investigation is part of an attempt to prove an old hypothesis, namely, that this increase in permeability is mediated by histamine. A comparative study was made of histamine, of the histamineliberator 48/80, a condensation product ofp-methoxyphenylethylmethylamine and formaldehyde (Baltzly, Buck, de Beer & Webb, 1949), and of leukotaxine (Menkin, 1936(Menkin, , 1938a.In animals with a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
271
2
3

Year Published

1955
1955
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(284 citation statements)
references
References 11 publications
8
271
2
3
Order By: Relevance
“…Substance P, a neurotransmitter which induces mast cell degranulation in some species (16), lacked activity as a mediator of enhanced permeability in sheep as has been reported in rabbits (17). The time course ofplasma leakage induced by histamine and bradykinin was similar to that reported in man (18), guinea-pigs (19) and rabbits (20). Platelet-activating factor showed a similar early peak in plasma leakage, however, in contrast to histamine and bradykinin, plasma leakage continued at an appreciable rate in the interval from 30-40 min.…”
Section: Discussionsupporting
confidence: 85%
“…Substance P, a neurotransmitter which induces mast cell degranulation in some species (16), lacked activity as a mediator of enhanced permeability in sheep as has been reported in rabbits (17). The time course ofplasma leakage induced by histamine and bradykinin was similar to that reported in man (18), guinea-pigs (19) and rabbits (20). Platelet-activating factor showed a similar early peak in plasma leakage, however, in contrast to histamine and bradykinin, plasma leakage continued at an appreciable rate in the interval from 30-40 min.…”
Section: Discussionsupporting
confidence: 85%
“…Feldberg and Miles (1953) injected compound 48/80 intravenously in guinea-pigs previously injected with pontamine blue, and observed that different areas of the skin were blued in proportion to their histamine content. Miles and Miles (1952) using the same stain showed intensified blueing of the cutaneous area injected with compound 48/80. This phenomenon was considered to be an effect of the released histamine since it was antagonized by mepyramine.…”
Section: Discussionmentioning
confidence: 99%
“…3A and B). To complement the angiogenesis assay, we also examined the effect of ZD6474 treatment upon vascular permeability in vivo using the Miles assay (30). Treatment of mice with ZD6474 decreased the vascular permeability induced by CM, VEGF, or EGF.…”
Section: Blockade Of Vegfr2 and Egfr Signaling Inhibits Angiogenesis mentioning
confidence: 99%